Peran Kepemimpinan Dan Budaya Sekolah Dalam Mewujudkan Keberhasilan Program Sekolah Sehat Dan Ramah Anak Di SD Negeri 013 Kecamatan Penajam Kabupaten Penajam Paser Utara - Rusmilawati; Ridwan, Muhammad; Rukaiyah, St (STIM-LPI Makassar, 2025)
This study aims to analyze the role of school leadership and school culture in achieving the success of the Healthy and Child-Friendly School program at SD Negeri 013 Penajam District, Penajam Paser Utara Regency. A qualitative descriptive research approach was employed, with data collected through in-depth interviews, observations, and document analysis. The informants included the principal, teachers, parents, and students directly involved in the program's implementation. The research findings indicate that school leadership plays a key role in the success of the Healthy and Child-Friendly School program. A democratic, innovative, and cooperative leadership style fosters an environment that supports active participation from all school stakeholders, including teachers, students, and parents. The principal actively provides motivation, formulates policies, and ensures the availability of supporting facilities such as a healthy canteen, health clinic (UKS), school gardens, and anti-bullying campaigns. Through the synergy between visionary leadership and a positive school culture, the Healthy and Child-Friendly School program at SD Negeri 013 has been effectively implemented, providing significant benefits for students in terms of health, well-being, and character building. This study recommends the sustainability of the program through regular evaluations, improved supporting facilities, and ongoing collaboration between schools, parents, and relevant stakeholders.